Review Literatur tentang Penerapan Model Pembelajaran Kooperatif pada Bola Voli di Pendidikan Jasmani - Sahabuddin, Sahabuddin (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
Volleyball instruction in physical education requires a pedagogical approach that develops both technical skills and students' social and motivational aspects. This literature review aims to analyze the effectiveness of implementing cooperative learning models—specifically STAD, TGT, Jigsaw, and their variations—in improving volleyball technical skills and students' affective outcomes. The review method was conducted systematically through a search of articles in Google Scholar, Scopus, Web of Science, PubMed, DOAJ, SINTA, and GARUDA databases published between 2015 and 2025. Keywords included cooperative learning models, volleyball, physical education, technical learning outcomes, and learning motivation. Of the 100 initial articles, 30 met the inclusion criteria and were analyzed thematically and narratively. The review results indicate that implementing cooperative learning models significantly improves volleyball technical skills—underhand passing (15–35%), overhand passing (10–28%), serving (12–30%), and smashing (10–25%). In addition to technical aspects, the cooperative learning model also has a positive impact on student motivation, cooperation, communication, and active participation. STAD is the most widely used model and the most consistent in improving students' technical performance and social aspects. Overall, these findings imply that the cooperative learning model is highly relevant for volleyball learning and worthy of integration into the Physical Education and Health curriculum. This review also emphasizes the need for further research with more robust experimental designs, longer intervention durations, and the use of modern learning technology.